2015
DOI: 10.4236/jep.2015.65051
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Particulate Matter Associated with Systemic Inflammation in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic disease characterized by progressive airflow obstruction, along with pulmonary and systemic inflammation. Outdoor PM has been associated with morbidity and mortality in COPD but less is known about effects of indoor air quality. In former smokers with COPD, we investigated in-home PM effects on pulmonary and systemic inflammation, symptoms, and lung function. Participants underwent in-home air monitoring for two weeks and simultaneous health assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This barrier contains placental transporters that can block or facilitate foreign compounds ( Myllynen et al 2005 ; Wick et al 2010 ). Further, it has been reported that air pollution was associated with increased white blood cells in chronic obstructive pulmonary disease (COPD) patients, suggesting that air pollutants can elicit systemic inflammation ( Bose et al 2015 ). In addition, it has been observed that human plasma collected from individuals exposed to diesel exhaust for only short periods of time (1 hr) is proinflammatory to endothelial cells in vitro ( Channell et al 2012 ), implying that soluble, proinflammatory mediators circulate in the blood after inhalation of diesel.…”
Section: Discussionmentioning
confidence: 99%
“…This barrier contains placental transporters that can block or facilitate foreign compounds ( Myllynen et al 2005 ; Wick et al 2010 ). Further, it has been reported that air pollution was associated with increased white blood cells in chronic obstructive pulmonary disease (COPD) patients, suggesting that air pollutants can elicit systemic inflammation ( Bose et al 2015 ). In addition, it has been observed that human plasma collected from individuals exposed to diesel exhaust for only short periods of time (1 hr) is proinflammatory to endothelial cells in vitro ( Channell et al 2012 ), implying that soluble, proinflammatory mediators circulate in the blood after inhalation of diesel.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Bose et al showed the correlations between indoor PM 2.5 and systemic inflammation in COPD patients. Yet such relationship was not found with coarse fraction of particles (PM 2.5−10 ) (Bose et al, 2015 ).…”
Section: Pm 25 Structure and Compositionmentioning
confidence: 98%
“…In low‐ and middle‐income countries such as Uganda, over 95% of the population relies on biomass fuel for heating, cooking, and lighting, with women and children disproportionately affected due to the time spent indoors during high‐exposure activities . Particulate matter, a component of indoor air pollution, is thought to be associated with adverse acute and long‐term respiratory effects including an increased risk of acute respiratory infections, chronic obstructive pulmonary disease, and lung cancer . For example, a dose–response relationship between indoor particulate levels and acute respiratory infections has been identified in rural Kenya, whereas a recent cross‐sectional study in rural Uganda has also identified a high prevalence of early‐onset chronic obstructive pulmonary disease in women, with exposure to biomass smoke being the major risk factor …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Particulate matter, a component of indoor air pollution, is thought to be associated with adverse acute and long-term respiratory effects including an increased risk of acute respiratory infections, chronic obstructive pulmonary disease, and lung cancer. 6,7 For example, a dose-response relationship between indoor particulate levels and acute respiratory infections has been identified in rural Kenya, 8…”
Section: Introductionmentioning
confidence: 99%